Reproduction of Rescued Vespertilionid Bats (Nyctalus noctula) in Captivity: Veterinary and Physiologic Aspects - Pikula, Jiri; Bandouchova, Hana; Kovacova, Veronika; Linhart, Petr; Piacek, Vladimir; Zukal, Jan (The veterinary clinics of North America. Exotic animal practice, 2017)
Long-term conservation and educational activities of numerous nongovernmental organizations have greatly increased public awareness about bats and their lifestyle. As a result, there is growing public concern about threats to bat populations. Many species of bats declined over recent decades and there is great demand for medical services to help injured or diseased bats. Veterinary clinicians dealing with such cases have to consider many issues, including ethical issues associated with the delayed fertilization reproduction strategy of temperate insectivorous bats. An outline of veterinary and physiologic requirements for treatment of and keeping vespertilionid bats in captivity is highlighted.
Keywords: Bat; Fertilization; Euthanasia; Torpor; Blood profile; Animals, Zoo; Male; Thermoregulation; Animals; Captive birth; zvířata v ZOO; Female; mužské pohlaví; ženské pohlaví; Ethics; Chiroptera; zvířata